Characterization of the technological infrastructure for peanut production in the Western region of São Paulo state - Neves, Fabiano Pinto [UNESP]; de Oliveira, Sandra Cristina [UNESP]; Neto, Mário Mollo [UNESP]; Mantovani, Leandro Paloma [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP] (Centro Universitario de Maringa, 2024)
Technological innovation is one of the differentiating factors for the competitiveness of Brazilian agribusiness and can significantly influence the productivity and sustainability of a crop. Peanut production is highly relevant to the State of São Paulo since this state is responsible for around 90% of national production. Thus, given the expressiveness and importance of this crop for agribusiness in São Paulo, the aim of this work was to characterize the technological production infrastructure of peanut farmers in the Western region of São Paulo State, which has the largest peanut production in the state. A form was applied to a sample of farmers in this region, considering the following parameters associated with technological adoption in the 2022/23 harvest: machines and equipment; inputs; storage; and management. Data were analyzed using descriptive statistics. The results showed that the majority of peanut farmers surveyed had an average productivity above the state average in this harvest. Furthermore, around half of these farmers use the self-propelled automotive sprayer, GPS, and section cutting on the sprayer, and all have harvesters. It should also be observed that almost 93% of them carry out annual soil analysis and 86% invest in the application of macrobiologicals. Furthermore, all interviewees use a dryer and warehouse to maintain peanuts, have agronomic assistance from a cooperative/reseller, and have a professional to manage the business. In this way, a preliminary scenario was shown on the adoption of Agriculture 4.0 technologies in peanut cultivation in the western region of São Paulo, and the potentiality for the use of certain technologies, that could provide a cleaner and more sustainable production and also useful information for the decision-making by the actors of the peanut production chain.
Caracterização da infraestrutura tecnológica para a produção de amendoim na região Oeste Paulista
Keywords: Agribusiness; Agriculture 4.0; Arachis Hypogaea L; Production infrastructure; Technologic innovation